2015
DOI: 10.1016/j.jvs.2014.07.033
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating and treating venous outflow stenoses is necessary for the successful open surgical treatment of arteriovenous fistula aneurysms

Abstract: There is a high association of venous outflow stenoses and AVFA. Comprehensive therapy should encompass treatment of any venous outflow stenoses before open AVFA repair. A two-stage repair may decrease tunneled hemodialysis catheter use in patients with multiple aneurysms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 12 publications
0
18
1
Order By: Relevance
“…These AVFAs are strongly associated with venous outflow stenosis. 3,4 In our series, 46.7% (Table I) of patients had such findings that required treatment at the time of AVFA revision.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…These AVFAs are strongly associated with venous outflow stenosis. 3,4 In our series, 46.7% (Table I) of patients had such findings that required treatment at the time of AVFA revision.…”
Section: Discussionmentioning
confidence: 61%
“…Aneurysm formation remains a commonly encountered complication that threatens the longevity of these conduits. 2,3 Whereas approaches for the successful management of AVF aneurysms (AVFAs) have been previously described, 4,5 there remains appreciable subsequent loss of these critical conduits due to subsequent complications of reintervention, such as thrombosis and infection. Extracellular matrix (ECM; Cor-Matrix, Roswell, Ga) is an approved vascular conduit with antimicrobial properties.…”
mentioning
confidence: 99%
“…Previously reported techniques for treatment of AFV pseudoaneurysms and aneurysms have included the use of self-expanding stent grafts [14], prosthetic graft exoprosthesis reinforcement [8], use of Tubularized CorMatrix [15], aneurysmorrhaphy [12], and partial aneurysmectomy with native reconstruction [9,16] or prosthetic interposition [17]. Patel et al [18], reported that they performed resection of the aneurysm, followed with graft interpositioning or primary repair and no fistulas were compromised or lost as a result of the procedure. Georgiadis et al [19], in a study which they performed aneursym excision and graft interposition with PTFE graft, reported that patency rates of the repaired AVF as nearly 70%.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, increased venous pressure may also result from stenosis within the central venous system and hasten aneurysm formation. Central venous stenosis typically results from extended central venous catheterisation and previously published studies suggest a broad range of incidence between 13% and 100% [15][16][17][18][19][20]. Imaging of the central venous system by fi stulography or ultrasound is not routine however, and potentially explains the wide incidence rates reported.…”
Section: Prevalence and Aetiologymentioning
confidence: 99%